Bhaddanta Jota Mahatherʻ cī cañʻ reʺ sāʺ ʼapʻ so Dhammacakrā Pāḷi toʻ ʼa cuṃ nhaṅʻʹ ta kva Mranʻ mā bhāsā pranʻ - Jota, ʼA rhaṅʻ (Haṃsāvatī Piṭakatʻ Puṃ nhipʻ tuikʻ, 1955)
Commentary with the Pali text, on Dhammacakkapavattanasutta, first sermon of Gautama Buddha.